Comparison Of Phylogenetic Trees Using Difference Distance Function Method - Maziah, Medin (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study is mainly about the construction of phylogenetic trees using for difference di stance functions methods. The purpose of the study is to do the comparison and analysis of the phylogenetic tree produced by the four distance functions in order to determine the correct and better phylogenetic tree. The comparison is done in line with the objective, to find the most accurate distance function. This study take in four algorithms of difference distance function which are the Pearson correlation coefficient, Euclidean distance, Manhattan distance and the Averaged dot product. The pre-processing is implemented using the Microsoft Visual C++. The phylogenetic tree is build using the PHYLlP (the PHYlogeny Inference Package), a package of programs for inferring phylogenies (evolutionary trees). PHYLIP contains program for reconstructing trees from distance matrices. The comparisons are based on the percentage of bootstrap values which represent its level of confidence. The highest percentage gained from the Pearson Correlation Coefficient distance function. 57%. The other function produced 54%. 52 % and 51 % level of confidence for Manhattan distance. Averaged 001 Product and Euclidean di stance correspondingly.